Responsible leadership and expatriation: The influence of national culture - Roque, H.C.; Ramos, M. (Handbook of research on entrepreneurship, innovation, and internationalization, 2019)
One of the consequences of globalization was the internationalization of organizations. In this context, expatriation has become fundamental for the competitiveness of the organizations. Training is indispensable to adjustment of expatriates in a new culture. Poor performance by expatriates compromises the success and competitive capacity of organizations. Like expatriation, responsible leadership is a very important topic. Responsible leadership can be the answer for a more ethical business in a context full of uncertainties. In literature there are a variety of definitions about responsible leadership. In spite of that, the relationship between leaders and stakeholders (internal and external) to achieve a common objective is vital. Leaders interact with different stakeholders with different costumes and culture. Knowledge of national idiosyncrasies is very important because these are a key element in the internationalization process as well as a factor of success in expatriation and responsible leadership.